Impacts of urban green infrastructure on attentional functioning: insights from an fMRI study - Jiang, Xiangrong; Hu, Yifan; Larsen, Linda; Chang, Chun-Yen; Sullivan, William C. (Frontiers in Psychology, 2023)
Multiple studies using various measures, technologies, and participant groups have found that exposure to urban green infrastructure can help alleviate the daily attentional fatigue that human experience. Although we have made significant progress in understanding the effects of exposure to urban green infrastructure on attention restoration, two important gaps in our knowledge remain. First, we do not fully understand the neural processes underlying attention restoration that exposure to urban green infrastructure elicits. Second, we are largely unaware of how typical patterns of urban green infrastructure, such as combinations of trees and bioswales, affect recovery from attentional fatigue. This knowledge is crucial to guide the design and management of urban landscapes that effectively facilitate attention restoration. To address these gaps in our knowledge, we conducted a controlled experiment in which 43 participants were randomly assigned to one of three video treatment categories: no green infrastructure (No GI), trees, or trees and bioswales. We assessed attentional functioning using functional Magnetic Resonance Imaging (fMRI) and the Sustained Attention Response Task (SART). Participants exposed to urban settings with trees exhibited improved top-down attentional functioning, as evidenced by both fMRI and SART results. Those exposed to urban settings with trees and bioswales demonstrated some attention-restorative neural activity, but without significant improvements in SART performance. Conversely, participants exposed to videos of urban environments without green infrastructure displayed increased neural vigilance, suggesting a lack of attention restoration, accompanied by reduced SART performance. These consistent findings offer empirical support for the Attention Restoration Theory, highlighting the effectiveness of tree exposure in enhancing attentional functioning. Future research should investigate the potential impact of bioswales on attention restoration.